The Spreading Flame: The Rise and Progress of Christianity from its First Beginnings to the Conversion of the English - Mundadan, A M (Journal of Dharma, 1981)
F. F. Bruce The Spreading Flame (The Rise and Progress of Christianity from its First Beginnings to the Conversion of the English), Grand Rapids, Michigan : Wm. B. Eerdmans Publishing Company, 1979 (reprint of 1958 edition : The Paternoster Pressh .